Une frontière virtuelle : l’exploitation des ressources minérales profondes dans le Pacifique - Pierre-Yves Le Meur; Valelia Muni Toke (VertigO, 2021)
The project to exploit deep mineral resources, which dates back to the 1960s, came back to the forefront in the 2000s, in a context of a race for raw materials and the rapid growth of emerging economies, particularly China. Deep-sea mining constitutes a new economic and technological frontier for mining firms and transnational capital, while Pacific Island Countries and Territories are striving to anticipate this encounter by strengthening their sovereign powers and regional cooperation. At stake for indigenous peoples and customary authorities is the cognitive and normative representation of oceanic spaces as an integral part of their universe and life world that feeds specific assertions of "non-Westphalian" sovereignty. However, the realization of the deep-sea mining potential remains slow to emerge. This article proposes to explore this still largely virtual mining frontier through the policies and mechanisms put in place in the French territories of the Pacific, with an emphasis on the case of Wallis and Futuna. It will examine and analyze the effects induced by the encounter between French policy, Oceanian responses and the virtuality of deep-sea mining, particularly from the point of view of the overseas territories' relations to the State and to information, between mistrust, rumor and controversies. The article will show the key role of uncertainty (moral, institutional and ontological) in how social actors understand and negotiate the issues raised by deep-sea mining prospects.